THE ROLE OF INFORMATION TECHNOLOGY IN IMPROVING THE QUALITY OF COMMUNICATION IN EDUCATIONAL INSTITUTIONS - Musthofa, Mohammad Dendy; Hefny, Hefny (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Abstract:              The development of information technology (IT) has had a significant impact on various aspects of life, one of which is in the world of education. Information technology plays an important role in improving the quality of communication in educational institutions by accelerating the flow of information, expanding the reach of communication, and increasing interactivity between related parties, such as educators, students, and parents. This study aims to analyze the role of information technology in supporting the effectiveness of communication in educational institutions. The methods used are literature reviews and observations of the implementation of communication technology in several educational institutions. The results of the study show that the use of digital platforms, learning management applications, and social media can accelerate the process of delivering information, facilitate two-way communication, and increase collaboration between teachers, students, and parents. In addition, the use of technology can also enrich learning resources, support distance learning, and facilitate more transparent and accountable learning evaluations. In conclusion, information technology has a strategic role in improving the quality of communication in educational institutions, which ultimately contributes to improving the quality of education itself.